The Effect of Addition of Combination of Plasma Treated Polyester and Polyamide Fibers on Surface Roughness and Some Mechanical Properties of Heat Cured Acrylic Resin - Fatalla, Abdalbseet A; Husham, Ghasak H; Abdullah, Zaynab S. (Journal of Baghdad College of Dentistry, 2018)
Background: Poly (methyl methacrylate) has several disadvantages (poor mechanical properties) like impact and transverse strength. In order to overcome these disadvantages, several methods were used to strengthen the acrylic resin by using different fibers or fillers. This study was conducted to evaluate the effect of Plasma treatment of the fiber on mechanical properties Poly (methyl methacrylate) denture base material.Materials and methods: Specimens were prepared from poly methyl metha acrylic (PMMA) divided according to present of fiber into 4 groups (first group without fiber as control group, second group with Plasma treated polyester fibers, third group with Plasma treated polyamide fibers and fourth group Plasma treated combination of polyester and polyamide fibers. The samples to be treated with oxygen gas plasmaResults: the results show that the highest mean values for all tests included in the study appeared in group IV (Plasma treated combination of polyester and polyamide fibers) except for the surface roughness test the highest mean values found in group III (Plasma treated polyamide fibers, and only polyamide fiber slight improved roughness and other group have no effect on surface roughness Conclusion The addition of plasma treated fiber ( polyester, polyamide and combination of both fiber) improve transverse, impact strength and hardness properties of denture base material and has no effect on surface roughness.